Analisis Filosofis tentang keilahian Roh Kudus dari sudut pandang anak muda Advent kolayinuk berdasarkan Yohanes 14:16 - matthew woran ramlen; Rudolf Weindra Sagala; Stimson Hutagalung; Rolyana Ferinia (JURNAL KADESI, 2021)
Today many adventurous youths understand the divinity of the Holy Spirit. Based on the background of the problem, the purpose of this study is to analyze the meaning of the divinity of the Holy Spirit from the perspective of young people based on John 14:16. In this study, qualitative researchers with a literature approach are using descriptive analysis studies based on the Historical Grammatical Method by prioritizing the Solah Skriptura principle, which means the Bible interprets itself. The results of the analysis show that many young people doubt the divinity of the Holy Spirit as God. By doubting the divinity of the Holy Spirit, young people are less active in attending services. And their hearts strayed from the righteousness of Christ. The mistake of young people is to doubt the divinity of the Holy Spirit, due to their lack of understanding about the Holy Spirit as the representative of Christ on earth. The Holy Spirit, Eternal, All-Knowing, All-Powerful and All-Present, so that the Holy Spirit fills us with power to live according to the will of Christ.